2003
DOI: 10.2169/internalmedicine.42.867
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Demyelination Syndrome: Reversible MRI Findings in Bilateral Cortical Lesions

Abstract: A 70-year-old man who suffered from osmotic demyelination syndrome (ODS) is presented. Dyspnea, pseudobulbar palsy and motor weakness were seen. MRI in the acute stage revealed focal abnormal high-signal lesions in the pons, thalamus and bilateral cortical areas on Tl-weighted and FLAIR images. With corticosteroid therapy he recovered from his dyspnea and severe pseudobulbar palsy, and the spastic quadriplegia gradually improved. One year later the brain lesions had disappeared on T1-, T2-weighted and FLAIR im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
2
13
0
1
Order By: Relevance
“…To our knowledge, seven cases with corticosubcortical lesions have been described in six reports that include MRI [4][5][6][7][8][9]. Reviewing those reports, we found that, consistent with Okeda's pathological classification, the two types of corticosubcortical OM lesions can also be discriminated on MRI.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…To our knowledge, seven cases with corticosubcortical lesions have been described in six reports that include MRI [4][5][6][7][8][9]. Reviewing those reports, we found that, consistent with Okeda's pathological classification, the two types of corticosubcortical OM lesions can also be discriminated on MRI.…”
Section: Discussionsupporting
confidence: 71%
“…Gocht et al [2] examined lesion distribution in 58 autopsy cases with OM and found cerebral corticosubcortical lesions in 15%. To the best of our knowledge, corticosubcortical lesions associated with OM have been unfamiliar clinically, and their imaging findings have been reported only sporadically [4][5][6][7][8][9]. Okeda et al [3] studied the pathological features of corticosubcortical lesions in autopsy cases with OM and reported two distinct subtypes of lesions: cortical and subcortical.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern is thought to represent resolution of acute edema, remyelination, and decreased astrocytic response, based on the restoration of increased axonal membrane permeability, deleterious intracellular cascades, and disturbance of axonal transport. 3,5,8,11,14,16) The MR findings in osmotic demyelination syndrome are not specific with inconsistent appearance. 9) One case of osmotic demyelination syndrome had persistent computed tomography findings even after clinical improvement.…”
Section: Central Pontine and Extrapontine Myelinolysis In An Infantmentioning
confidence: 99%